Sintomas de Cancro Citrico en Arboles de Vivero - Timothy D. Riley; Megan M. Dewdney; Jamie D. Burrow (EDIS, 2018)
This 2-page Spanish-language publication that discusses citrus canker symptoms is a minor revision. Written by Timothy D. Riley, Megan M. Dewdney, and Jamie D. Burrow, and published by the Plant Pathology Department, July 2018.